Concept of a New Method for Determining the Transverse Profile of Wide-Aperture Beams; Charged & Neutral Particles Channeling Phenomena – Channeling 2029 - Bulavskaya A. A. Angelina Aleksandrovna; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich (2023, 2023)
This study describes the concept of a method for the measurement of flux density distribution in the transverse plane of wide-aperture beams such as radiotherapeutic medical beams